If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -10 = 62 + 2m Reorder the terms: -10 + 8m = 62 + 2m Solving -10 + 8m = 62 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -10 + 8m + -2m = 62 + 2m + -2m Combine like terms: 8m + -2m = 6m -10 + 6m = 62 + 2m + -2m Combine like terms: 2m + -2m = 0 -10 + 6m = 62 + 0 -10 + 6m = 62 Add '10' to each side of the equation. -10 + 10 + 6m = 62 + 10 Combine like terms: -10 + 10 = 0 0 + 6m = 62 + 10 6m = 62 + 10 Combine like terms: 62 + 10 = 72 6m = 72 Divide each side by '6'. m = 12 Simplifying m = 12
| -11x+9=185 | | x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 | | 3(-2y)+y=-10 | | 18-x=1 | | y=-16-16 | | -2(3y+4)=20 | | -1/3+1= | | 8y-2y+13=2y+12 | | 5w^2-6w+17=8 | | 6x^3-77x^2+56x+8=0 | | 48y-4(6-y)=12(3y+2) | | -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) | | x(7)=49 | | 2x^2=5-5x | | 3(2x-1)+9=2(3x+3) | | y=28(3)+10 | | 3.2-1.8x=-1.3 | | X^2+10=-25 | | -2x-7(-8x-16)=4 |